Peranan Salat Fardu Terhadap Manajemen Stres Mahasiswa PSKPS ULM 2023 - Ahmad Najmuddin Rafid; Farhan Yazid Rahmadani (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
Every believing Muslim is required to perform his/her obligation, which is Salat. Prayer is not necessarily just to be done without a purpose and benefits, one of which is to reduce stres. In the environment of many tasks, busy lecture schedules, exams, poor time management and social problems cause stres among students. This study uses a qualitative method with sample criteria, namely ULM 2023 PSKPS students who are Muslim. Based on the results obtained, it is evident that prayer plays a significant role in stres management for PSKPS ULM 2023 students. Prayer can reduce the causes of stres itself, namely dissatisfaction and disappointment. In addition to stres, prayer can also overcome anxiety, depression, and other mental disorders that can affect the health of PSKPS ULM 2023 students.